Comparison of osteogenic differentiation of embryonic stem cells and primary osteoblasts revealed by responses to IL-1β, TNF-α, and IFN-γ - Sidney, Laura E.; Kirkham, Glen R.; Buttery, Lee D.K. (Mary Ann Liebert, 2013)
There are well-established approaches for osteogenic differentiation of embryonic stem cells (ESCs), but few show direct comparison with primary osteoblasts or demonstrate differences in response to external factors. Here, we show comparative analysis of in vitro osteogenic differentiation of mouse ESC (osteo-mESC) and mouse primary osteoblasts. Both cell types formed mineralized bone nodules and produced osteogenic extracellular matrix, based on immunostaining for osteopontin and osteocalcin. However, there were marked differences in the morphology of osteo-mESCs and levels of mRNA expression for osteogenic genes. In response to the addition of proinflammatory cytokines interleukin-1β, tumor necrosis factor-α, and interferon-γ to the culture medium, primary osteoblasts showed increased production of nitric oxide (NO) and prostaglandin E2 (PGE2) at early time points and decreases in cell viability. In contrast, osteo-mESCs maintained viability and did not produce NO and PGE2 until day 21. The formation of bone nodules by primary osteoblasts was reduced markedly after cytokine stimulation but was unaffected in osteo-mESCs. Cell sorting of osteo-mESCs by cadherin-11 (cad-11) showed clear osteogenesis of cad-11(+) cells compared to unsorted osteo-mESCs and cad-11(-) cells. Moreover, the cad-11(+) cells showed a significant response to cytokines, similar to primary osteoblasts. Overall, these results show that while osteo-mESC cultures, without specific cell sorting, show characteristics of osteoblasts, there are also marked differences, notably in their responses to cytokine stimuli. These findings are relevant to understanding the differentiation of stem cells and especially developing in vitro models of disease, testing new drugs, and developing cell therapies.